A Legal and Criminological Analysis with Prevention Measures in Mind for the General Elections - Lianingsih, Nestia; Yohandoko, Setyo Luthfi Okta; Laksito, Grida Saktian (International Journal of Humanities, Law, and Politics, 2024)
The crime of money politics is a serious challenge in the election system, affecting the integrity of democracy and public trust. This article analyzes the phenomenon of money politics from a legal and criminological perspective, and identifies the driving factors and their impact on the political process. Apart from that, the article also offers prevention strategies that involve strict regulations, law enforcement officials with integrity, fair trials, the active role of the Election Supervisory Agency (Bawaslu), and comprehensive political education. It is hoped that these steps can help overcome and prevent criminal acts of money politics to ensure clean and democratic general elections